Towards gender equity in feminized disciplines. A qualitative research study in Chile. - Bernales, Margarita; González-Agüero, Marcela; Lucchini-Raies, Camila; Grau, Olaya; Ferrer, Lilian; Jones, Caroline Bradbury (Investigación & Educación en Enfermería)
Objective. To explore the gender equity indicators identified by female academics in feminized disciplines within a Chilean university and propose institutional strategies to promote gender equity. Methods. A qualitative study was conducted with 23 participants from four feminized disciplines at a Chilean university. Data were collected via semi-structured interviews and focus groups and analyzed using thematic analysis with the support of NVivo software. Results. Two major thematic axes emerged: (1) structural gender dynamics and power relations in feminized disciplines -Gender Roles, Feminized Fields as Service Disciplines, Interpersonal Dynamics Among Women and the Inclusion of Men-, and (2) building gender equity through contextsensitive indicators - leadership distribution, academic progression, research output, work-life/time use balance, and fair remuneration-, including final recommendations. Conclusions. Gender equity in feminized disciplines cannot be achieved solely through numerical parity. Institutional policies must address the hermeneutical injustice that renders women’s care and administrative labor invisible. Achieving equity requires integrating context-appropriate indicators into evaluation systems that formally recognize and value the multidimensional contributions of women in academia.